EFFECT OF PARTICIPATION OF BUDGET PREPARATION ON PERFORMANCE OF SKPD APPARATUS (Case Study In Local Government of Manado City) - Waney, Mekson; Pontoh, Winston (ACCOUNTABILITY, 2017)
The performance of an officer will be seen when he is involved in budgeting so that the budget set will be the correct reference in accordance with regional needs rather than on the interests of the authorities. The performance of the apparatus is largely determined by financial management, which includes budgeting. Inadequate budget formation can be demonstrated by the placement of apparatus based solely on proximity and personal relations factors, personnel who only prioritize personal or short-term interests, the occurrence of budget slack, do not involve fully to the financial management official in the preparation of budget and the time of budget preparation done just a few days. This study aims to determine the effect of budgetary participation on apparatus performance in SKPD in Manado City. The population in this study is 7,811 employees/apparatus that exist in 43 SKPD at Manado City Government. The sample chosen using purposive sampling method, that is 84 employees/apparatus having position as secretary, head of section, head of sub section. For the primary data tested came from 78 respondents from 84 respondents who set. The method of analysis used is simple linear regression analysis, before the data to be processed first tested by using the classical assumption test. While for data processing research using computer program SPSS version 15.0. The test results showed the participation of budgeting have an effect on significantly on apparatus performance at SKPD in Manado City Government. This is obtained from the results of the t test which shows a significance level of 0.000 (less than 0.005).Keywords: Participation of budget preparation, apparatus performance